Implementasi Pendekatan Science, Technology, Engineering, Mathematics (STEM) dalam Pembelajaran dan Hubungannya dengan Kemampuan Berpikir Ilmiah Siswa - Septu Yoelianty Sukma; Zulyusri Zulyusri; Ardi Ardi; Heffi Alberida (AS-SABIQUN, 2022)
STEM is an integrated learning approach in sciene, technology, and mathematics. In 1990 NSF (National Science Foudation) introduced the STEM approach with the aim of forming a generation that is able to fulfill 21st century abilities such as scientific thinking, reasoning, logical, systematic, and able to improve communicative, collaborative and problem solving, abilities. Students scientific thinking skills need to be developed to form students who think scientically, reason, logicaaly, systematically, and are able to solve problems by collecting information using scientific methods such as exam ination and reasoning, logically, in taking action. Students have various levels of thin king. The purpose of this study is to examine the results of liteture review research method using several data sources such as books and articles from electronic journals. The results of the research show that the application of the STEM approachin learning affects the improvement of students scientific thinking skills.